Вплив магматичних порід Вигорлат-Гутинського вулканічного пасма на час пробігу сейсмічних хвиль - Козловський, Е.; Малицький, Д.; Парфенюк, А.; Грицай, О.; Тимощук, В.; Ярема, І.; Асташкіна, О.; Махніцький, М. (Геоінформатика, 2017)
Уточнення швидкісних моделей під сейсмічними станціями Закарпаття важливе для уточнення визначених механізмів джерел землетрусів. Механізми вогнищ землетрусів визначають за стандартною швидкісною моделлю для певної сейсмічної станції Закарпаття, зазвичай однаковою для всіх станцій. Проте значення швидкостей поширення сейсмічних хвиль у середовищі суттєво впливають на розрахунок кута виходу сейсмічної хвилі, на основі якого визначають механізм джерела землетрусу. Тому для уточнення цього механізму важливо не використовувати стандартну швидкісну модель, а розраховувати швидкість пробігу сейсмічної хвилі в шарах для кожної сейсмічної події, оскільки вони можуть суттєво різнитися і, відповідно, впливати на визначення кутів виходу прямих I-хвиль із вогнища на станцію. На прикладі події, що відбулась 17.10.2006 р. (φ = 48,61° N, λ = 22,46° E, ζ = 24140м, h = 3300м ) показано, що вплив магматичних порід Вигорлат-Гутинського вулканічного пасма значно зменшує час пробігу сейсмічних хвиль у осадовому шарі та частково у фундаменті. Рассмотрено уточнение скоростей пробега сейсмических волн в первом и втором слоях для сейсмических событий, зарегистрированных сейсмостанциями Мукачево, Брод и Нижнее Селище за период с 2002 по 2013 г. с учетом влияния магматических пород Вигорлат-Гутинской вулканической гряды. Уточнение скоростных моделей под сейсмическими станциями Закарпатья важно для уточнения исследуемых механизмов источников землетрясений. Для определения механизмов очагов землетрясений используется стандартная скоростная модель на конкретной сейсмической станции Закарпатья. Однако значения скоростей распространения сейсмических волн в среде существенно влияют на расчет угла выхода сейсмической волны, на основе которого определяется механизм источники землетрясения. Поэтому для уточнения механизма источника землетрясения важно не применять стандартную скоростную модель, а рассчитывать скорости пробега сейсмической волны в слоях для каждого сейсмического события, так как они могут существенно различаться в зависимости от азимутов станций и углов выхода прямых Р-волн из очага на станцию. На примере события, которое состоялось 17.10.2006 р. (φ = 48,61° N, λ = 22,46° E, ζ = 24140 м, h = 3300 м), показано, что влияние магматических пород Вигорлат-Гутинской вулканической гряды значительно уменьшает время пробега сейсмических волн в осадочном слое и частично в фундаменте. The purpose of this work is to clarify the velocity of seismic waves propagation in the first and second layers for seismic events recorded by the seismic stations “Mukachevе”, “Brid” and “Nyzhnie Selysche” for the period from 2002 through to 2013 with the influence of magmatic rocks of the Vygorlat-Hutyn volcanic ridge. The investigation is important in determining and specifying the focal mechanisms of earthquakes.
Methodology. To determine the focal mechanisms of the earthquake, use is commonly made of the standard velocity model for a particular Transcarpathian seismic stations. However, the value of the velocity of seismic waves propagation in the medium has a significant impact on the calculation of the take-off angle of seismic wave, which is one of the major parameters for determining the focal mechanism of earthquakes. Therefore, to clarify the earthquake focal mechanism it is necessary to use a non-standard velocity model and calculate the velocity of the seismic waves propagation in layers for each seismic event, as they can vary widely depending on the azimuth of the stations and the take-off angles of direct P-wave from the source to station.
Findings. The example of the events that took place 17.10.2006. ( φ= 48,61° N, λ = 22,46° E, ζ = 24140 m, h = 3300 m) shows that the impact of magmatic rocks Vygorlat-Hutyn volcanic ridge reduces the propagation time of seismic waves in the sedimentary layer and partially in the basement.
Practical value. To determine the focal mechanism of the earthquake, we are to consider velocity of seismic waves in the layers for each individual case but not the standard velocity model under seismic stations.